Perception On the Quality of Life of Families with Children With ASD Condition - Huaiquián-Billeke, Claudia; Padilla-Marchant, Marianne; S, Jorge Oyarce; Gutiérrez-Saldivia, Ximena (International Journal of Membrane Science and Technology, 2023)
This is a qualitative study that addresses the perceptions on the quality of life of families with children with Autism Spectrum Disorder (ASD), who are cared for in an early care center of a regional university in Temuco, Chile. The research is based on a constructivist paradigm with a single case design. Semi-structured, in-depth interviews were used for data collection, and the analysis was carried out through open and axial coding, using ATLAS.ti 8.0 software. The results show that the ways in which families cope with this are conditioned by the diagnosis and level of support according to the DSM-5 that their son or daughter with ASD needs, which has repercussions on their family dynamics, which in turn conditions the expectations on the development, on their achievements and, especially, on the self-realization of their son or daughter. Given that extremes are chosen, overprotection stands out, where there is a lot of dependence and, on the other hand, a very permissive parenting style, where parents or caregivers associate all behavior to the condition and do not understand that not all behaviors are due to the condition, but that it also depends on the upbringing, routines and access to support networks.